Drawing from the insights of biology, sustainable healthcare systems should prioritise robustness over optimisation - Lecocq, Dan (Nursing philosophy, 2024)
The concept of performance has gradually become established in health policies. Presented as necessary and positive, it is often reduced to efficiency, which results in policies and management styles aimed at optimisation. While they are supposed to guarantee the sustainability of our healthcare systems, these practices have made them fragile. Insights from the life sciences help us understand why. Indeed, biologists observe that living beings do not prioritise optimisation but robustness. To cope with fluctuations, a robust organisation operates with redundancies, apparent waste, heterogeneity, organised fluctuations, slowness, and hesitation. It functions sub-optimally. This article offers a theoretical reflection and management directions for more robust healthcare systems.